PENGARUH ORIENTASI PASAR DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP KINERJA PEMASARAN MELALUI KEUNGGULAN BERSAING (Studi Kasus Pada Warung Makan Sekitar Alun-alun Di Kota Sragen - Santoso, Baharudin Yakub Didik; Sugiarto, Yohanes (Faculty of Economics and Business Diponegoro University, 2016)
The purpose of this study was to analyze the influence of market orientation and customer relationship management on marketing performance with a competitive advantage as intervening. Population and sample in this research is food vendors in food stalls around the square in the town of Sragen of 60 sellers of food stalls. The sampling technique in this study was done by using census or saturated sample. Is the primary data type. Methods of data collection using the questionnaire. The analysis technique used is path analysis. The research results showed that : Market orientation affect on competitive advantage. Customer relationship management affect on competitive advantage. Market orientation affect on performance marketing. Customer relationship management affect on performance marketing. Competitive advantage affect on marketing performance. Competitive advantage becomes the mediating variable between market orientation on performance marketing. Competitive advantage becomes the mediating variable between customer relationship management on performance of marketing